Forecasting market movement in Dhaka Stock Exchange: LSTM vs. ARIMA - Chakraborty, Pranjal (Brac University, 2019)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Science in Applied Economics, 2019.